Penelitian dan Akuntabilitas Keuangannya - Ani Wilujeng Suryani; Yongky Teguh Setiaji; Prihatini Retnaningsih; Imam Alfianto (Penerbit Goodwood, 2025)
Purpose: The case of manipulation in preparing financial reports in research carried out by university lecturers is a serious problem. This study aims to investigate the causes of lecturers having lack of accountability in their research financial reporting Methodology/approach: The systematic review method is used to conceptually explore why lecturers commit dishonest actions in financial reporting. The articles analyzed were 48 national and international journal articles from the Sinta and Google Scholar databases. Results/findings: The results show that fraud is influenced by information asymmetry, weak monitoring, and workload pressure from tridarma and publication demands. Universities should simplify reporting and enhance monitoring, while lecturers need work-life balance to reduce stress and improve accountability. Conclusion : Lecturers’ financial reporting issues stem from asymmetry, poor monitoring, and pressure. Improving oversight and work-life balance can enhance accountability. Limitations: : This study is limited to a literature review without primary data, so it cannot directly assess lecturers' understanding of financial accountability. Future research should use surveys or interviews. Contribution: This study confirms agency theory by highlighting information asymmetry and weak monitoring in universities. It provides a policy basis to enhance lecturer accountability, reduce fraud, and promote financial accountability and work-life balance.